(untitled) (Gestión y Gerencia, 2024)
The research analyzes the limitations of the Gross Domestic Product (GDP) as an economic indicator at a global level and the conceptual deficiencies and methodological inaccuracies in the Venezuelan case. We show that the United Nations System of National Accounts (SNA), designed for market economies, very superficially considers the existence of natural resources and their impact, an omission that gives rise to serious and inconvenient distortions, hiding the oil and rent-seeking nature of the Venezuelan economy. The statistics reported by the Central Bank of Venezuela (BCV), following the SCN, mistakenly take a portion of oil income as if it were production effort, overestimating GDP. From this overestimation arise errors of interpretation and sub-optimal decisions in the formulation of public policies. This analysis allows us to show frequent interpretation errors induced by the distortion in the composition of time series related to the oil GDP (GDPp), which excludes variations in the price of a barrel. It is concluded that it is necessary to separate the International Petroleum Income (RPI) accounts from the GDPp accounts for the sake of a fair characterization of the phase of the cycle through which the economy is passing.